2020
DOI: 10.3389/fonc.2019.01493
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-Occurring Invasive Urothelial Carcinoma in Dogs, a Unique Model to Drive Advances in Managing Muscle Invasive Bladder Cancer in Humans

Abstract: There is a great need to improve the outlook for people facing urinary bladder cancer, especially for patients with invasive urothelial carcinoma (InvUC) which is lethal in 50% of cases. Improved outcomes for patients with InvUC could come from advances on several fronts including emerging immunotherapies, targeted therapies, and new drug combinations; selection of patients most likely to respond to a given treatment based on molecular subtypes, immune signatures, and other characteristics; and prevention, ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 175 publications
1
89
0
Order By: Relevance
“…EGFR is overexpressed in both human and canine invasive transitional cell carcinoma (TCC) in about 75% of the cases 17 , 46 , 47 . Several EGFR-targeting compounds have been or are currently evaluated in clinical trials of human TCC, but so far with mixed results 17 . Recently, a particular 67-gene signature has been associated with sensitivity to EGFR inhibition in human bladder cancer cell lines 48 .…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…EGFR is overexpressed in both human and canine invasive transitional cell carcinoma (TCC) in about 75% of the cases 17 , 46 , 47 . Several EGFR-targeting compounds have been or are currently evaluated in clinical trials of human TCC, but so far with mixed results 17 . Recently, a particular 67-gene signature has been associated with sensitivity to EGFR inhibition in human bladder cancer cell lines 48 .…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…1 Due to its high malignancy, invasiveness, and metastatic potential, TCC is difficult to treat in dogs, despite the availability of intensive multimodal therapies, including surgery, chemotherapy, radiation therapy, and palliative laser ablation. 2,3 Particularly, in dogs with urethral TCC, complete surgical excision is unrewarding because of the location of the tumor, and thus, drugs are the main treatment modality for canine urethral TCC. 4 To our knowledge, there currently is no effective longterm single therapy for the treatment of urethral TCC in dogs; thus, the development of novel therapeutic strategies for urethral TCC, including molecular-targeted therapy, is highly anticipated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is a realistic possibility that pet dogs ( Canis lupus familiaris ) will play an expanding role in such testing, given the parallels of some naturally‐arising canine cancers, such as osteosarcoma, glioma, urothelial carcinoma and non‐Hodgkin lymphoma (NHL), to their human counterparts (reviewed in Refs. 1‐8). Studies with CAR T cells and PD‐1/PD‐L1 blockade have been reported 9‐11 .…”
Section: Figurementioning
confidence: 99%